Pengaruh Kenaikan Harga Bahan Pangan terhadap Inflasi - Bafadal, Azhar (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
This study aimed to analyze the effect of price increase for commodity group, commodity sub-group and commodity on inflation in Kendri city. Data used were of monthly time series data Bank Indonesia and Central Board of Statistic, covering January 2002-August 2011. The analysis was undertaken using multiple regression. The research results showed that the group of processed food, beverages, and tobacco product gave more effect on inflation compare to the group of foodstuff. The increasing of 1% of the group of processed food, beverages, and tobacco product would effect to inflation by 0,69%, and the group of foodstuff effect on inflation by 0,34%. In the group of foodstuff, the sub-group of fresh fish gave the most effect on inflation. The increasing of sub-group of fresh fish gave the effect to inflation by 0,30%, meanwhile, the most little effect to inflation was contributed by processed fish (0,02%). The increasing of rice price to inflation was not great, where 1% of rice price increased inflation by 0,08%.